War Trauma and Traumatized Characters in A Farewell to Arms by Ernest Hemingway - Asst. Lect. Mohammed Abdulbasit Ibrahim (مجلة النور للدراسات الانسانية)
This article examines war trauma and its psychological imprint on characters in Ernest Hemingway's A Farewell to Arms (1929) through psychoanalytic theories and trauma studies. Drawing from foundational theories of trauma by Sigmund Freud the analysis emphasizes the repetitive, self-destructive patterns of behavior exhibited by traumatized individuals. Hemingway's portrayal of Lieutenant Frederic Henry and Catherine Barkley reflects the profound psychological toll of WWI, presenting their struggles as emblematic of the broader human condition in the post-war period.